Analysis of Fusion Reactions and Subsequent Decay Mechanisms at Low Energy Regime - Sharma, Ishita (My University, 2020)
In the present thesis, an extensive study of heavy ion induced reactions is carried out in reference to fusion and subsequent decay processes. The analysis is done at energies across the Coulomb barrier and related anomalies are addressed ade- quately. Different methodologies are used to estimate the reaction dynamics. For the fusion process, Wong and l-summed Wong model are applied, whereas, for the decay process dynamical cluster-decay model is used. In both the processes, nuclear interaction potential plays the eminent role, which is obtained either by Skyrme en- ergy density formalism or via proximity theorem based proximity potential. Hence, the role of different nuclear interactions along with deformations, orientations, an- gular momentum, incident energies, N/Z effect are examined in the framework of Wong/l-summed Wong and DCM model. The thesis is organized in eight chapters, the brief account of which is discussed below.
Keywords: Fusion; Skyrme forces